The Long-Term Efficacy and Safety of Carotid Artery Stenting among the Elderly: A Single-Center Study in China - Lan Wen; Suxia Wang; Lei Liu; Lin Chen; Jia Geng; Lei Kuang; Gangzhen Qian; Junjie Su; Kangning Chen; Zhenhua Zhou (Behavioural Neurology)
Compared to carotid endarterectomy, carotid artery stenting (CAS) is reportedly associated with higher perioperative risks in elderly patients. To verify the long-term safety and efficacy of CAS with embolic protection in elderly patients, we retrospectively reviewed the medical records of patients with carotid stenosis treated between January 2003 and March 2010 at the Department of Neurology of a large university hospital in China. We included patients with symptomatic, moderate, or severe carotid stenosis of atherosclerotic etiology (other etiologies were excluded), with a disability score ≤ 3 on the modified Rankin Scale, and who received CAS instead of carotid endarterectomy. The clinical endpoints studied were stroke recurrence and all-cause death. The 84 patients included in this study (median follow-up, 8.08 years) were stratified according to age at surgery (<70 vs. ≥70 years), and no significant between-group difference was found regarding baseline characteristics. Of the 14 patients (16.67%) who experienced a defined clinical endpoint, 4 (7.14%) were aged <70 years and 10 (35.71%) were aged ≥70 years (P=0.002). Overall mortality was 14.29% (12/84), with 3 (5.36%) and 9 (32.14%) deaths among patients aged <70 and ≥ 70 years, respectively (P=0.002). Heart disease and cancer accounted for most deaths. The two groups did not differ regarding stroke recurrence, disability score, or rate of in-stent restenosis (blockage ≥ 50%), but patients aged ≥70 years had a higher risk of mortality (odds ratio, 8.3684; 95% confidence interval, 2.048–34.202; P=0.003), and age was an independent risk factor for death (odds ratio, 20.054; 95% confidence interval, 3.094–129.987, P=0.002). Among elderly patients in Southwest China, CAS can effectively prevent stroke recurrence without increasing the risk of stroke-related death, but the risk of all-cause death is higher, with age as an independent risk factor. Careful patient selection is of key importance in the treatment of symptomatic carotid artery stenosis.